Ihrig Thanks Backers of CMA Continuance - Vallejo Times-Herald (Vallejo Times-Herald)
Commo. Russell M. Ihrig, USN, Ret., superintendent of the Ca1ifornia Maritime Academy, issued today a statement reogarding the favorable decision of the Ways and Means Committee of the State Assembly to continue the academy in operation and to approve the forthcoming annual budget.